Modal Sosial Warga Kelurahan Banyu Urip Kota Surabaya Dalam Program Wani Jogo Suroboyo - Fransiska Sune; Azizah Alie; Yelly Elanda (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2023)
This study examines the use of social capital in the Suroboyo wani jogo program. Surabaya managed to go through a crisis during the Covid 19 pandemic. This was because there was synergy between the programs initiated by the city of Surabaya and the social capital owned by the community. One of the sub-districts that have successfully run the wani jogo program in Suroboyo is the Banyu Urip sub-district, Surabaya City. Social capital is the key to the success of the program. This study uses a qualitative method with a narrative approach. James Coleman's theory of social capital as an analytical knife in this study. Data obtained from in-depth interviews, literature study, observation and documentation. There are five informants interviewed in this study. The informant determination technique uses a purposive technique by determining the criteria to be used as an informant. The study of social capital in the city of Surabaya is interesting to discuss because social capital in urban areas tends to be eroded. However, the research results show that the social capital owned by residents in the city of Surabaya is still high, especially in the Banyu Urip sub-district. The social capital owned by residents of the Banyu Urip sub-district can be seen from the success of the Suroboyo wani jogo program when the co-19 pandemic occurred. The use of social capital in the form of trust, norms/values and networks is used in the four activities of the wani jogo Suroboyo program. The four activities of the Wani Jogo Suroboyo program include the Wani Sehat, Wani Sejahtera, Wani Ngandani, and Wani Jogo programs. Each activity has different values/norms, levels of trust and networks. With the social capital they have, residents of the Banyu Urip sub-district are able to suppress and prevent the spread of Covid 19.